PENINGKATAN MASA SIMPAN DAN DAYA TERIMA BANDENG ASAP DENGAN MENGGUNAKAN METODE PENGERINGAN - Leersia Yusi Ratnawati (Fakultas Kesehatan Masyarakat, Universitas Jember, 2007)
Smoking and drying are one of food processing and preservation with high temperature. The principle of smoke chanos-chanos preservation with drying method is to get hold of bacterial activity and storage time become more longer. Food processing with high temperature can influence storage time and organoleptic of food (smoke chanos-chanos). The purpose of this research was to know the influence of smoke chanos-chanos drying time to storage time and organoleptic. This research was a true experimental study with randomized complete block design. The sample was 25 smoke chanos-chanos that shared become 5 group, i.e: control group (P0), group with 8 hours drying (P1), group with 10 hours drying (P2), group with 12 hours drying (P3) and group with 14 hours drying (P4). Statistical analysis to know the influence of smoke chanos-chanos time drying to storage time was used One-way Manova test. And Kruskal-Wallis test was used to know the influence of smoke chanos-chanos time drying to organoleptic with α=0,05. Result of research showed that 14 hours drying (P4) could increase storage time of smoke chanos-chanos become 5-6 days. Manova test showed that drying time influenced storage time (p=0,000). And, Kruskal Wallis analysis showed the influenced of drying time to organoleptic score. Conclusion of research is smoke chanos-chanos drying time influenced storage time and organoleptic score. Therefore, it is suggested to give modification treatment by drying process to increase storage time and organoleptic score. Keywords: smoke chanos-chanos, drying process, strorage time, organoleptic score